Harry Potter and the goblet of fire - Radcliffe, Daniel, 1989-; Newell, Mike, 1942-; Watson, Emma, 1990-; Grint, Rupert, 1988-; Smith, Maggie, 1934-; Oldman, Gary.; Pratt, Roger; Doyle, Patrick, 1953-; Rowling, J. K.; Warner Home Video (Firm) ([Burbank, CA] : Warner Home Video, 2006)
Harry's fourth year at Hogwarts is marked by the Quidditch World Cup and the Triwizard Tournament, in which student representatives from three different wizarding schools compete in a series of increasingly challenging contests. However, Voldemort's Death Eaters are gaining strength and create the Dark Mark - giving evidence that the Dark Lord is ready to rise again. In the unsuspecting lives of the students at Hogwarts, the competitors are selected by the goblet of fire, which this year makes a very surprising announcement: Hogwarts will have two representatives in the tournament, including Harry. Now Harry has to rise to the challenge for the Tri Wizard Tournament while keeping up with school.
DVD; region 1 encoding; widescreen presentation; dual-layer format.
Closed-captioned; dialogue in English (5.1 Dolby Surround) or Spanish (5.1 Dolby Surround) with optional subtitles in English, French or Spanish.
Daniel Radcliffe, Emma Watson, Rupert Grint, Maggie Smith, Gary Olman, Miranda Richardson, Ralph Fiennes, Alan Rickman, Jason Isaacs.
Director of photography, Roger Pratt ; art directors, Mark Bartholomew ... [et al.] ; editor, Mick Audsley ; music, Patrick Doyle ; costume designer, Jany Temime ; production designer, Stuart Craig ; visual effects supervisors, Tim Burke, Charley Henley, Jim Mitchell, Stuart Pitcher ; special effects supervisor, Dominic Tuohy.
Based on the novel by J.K. Rowling.
Originally released as a motion picture in 2005.
Keywords: Potter, Harry (Fictitious character) -- Drama; Hogwarts School of Witchcraft and Wizardry (Imaginary place) -- Drama; Contests -- Drama; Feature films; Adventure films; Fantasy films; Adventure -- Feature; Fantasy -- Feature; Video recordings for the hearing impaired; Videodiscs